2014
DOI: 10.1002/adma.201401959
|View full text |Cite
|
Sign up to set email alerts
|

A 4‐Fold‐Symmetry Hexagonal Ruthenium for Magnetic Heterostructures Exhibiting Enhanced Perpendicular Magnetic Anisotropy and Tunnel Magnetoresistance

Abstract: A 4-fold-symmetry hexagonal Ru emerging in epitaxial MgO/Ru/Co2 FeAl/MgO heterostructures is reported, in which an approximately Ru(022¯3) growth attributes to the lattice matching between MgO, Ru, and Co2 FeAl. Perpendicular magnetic anisotropy of the Co2 FeAl/MgO interface is substantially enhanced. The magnetic tunnel junctions (MTJs) incorporating this structure give rise to the largest tunnel magnetoresistance for perpendicular MTJs using low damping Heusler alloys.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 35 publications
2
57
0
Order By: Relevance
“…The large magnitude of K v probably originates from a tetragonal distortion of the Co 2 Fe x Mn 1−x Si lattice due to a lattice mismatch between the Pd under layer (or the MgO capping) and Co 2 Fe x Mn 1−x Si alloy. The values of K s /t are also listed in Table 2, which are about 19 × 10 6 erg/cm 3 and are comparable values with the previously reported PMA-Co 2 FeAl lms 20,23) . There are two different interfaces which can provide anisotropy energy for the Heusler alloy layer, namely, Co 2 Fe x Mn 1−x Si/ MgO interface (top interface) and Pd/Co 2 Fe x Mn 1−x Si interface (bottom interface).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The large magnitude of K v probably originates from a tetragonal distortion of the Co 2 Fe x Mn 1−x Si lattice due to a lattice mismatch between the Pd under layer (or the MgO capping) and Co 2 Fe x Mn 1−x Si alloy. The values of K s /t are also listed in Table 2, which are about 19 × 10 6 erg/cm 3 and are comparable values with the previously reported PMA-Co 2 FeAl lms 20,23) . There are two different interfaces which can provide anisotropy energy for the Heusler alloy layer, namely, Co 2 Fe x Mn 1−x Si/ MgO interface (top interface) and Pd/Co 2 Fe x Mn 1−x Si interface (bottom interface).…”
Section: Resultssupporting
confidence: 74%
“…Recently, the number of reports of PMA lms using Co-based full-Heusler alloys further increases. Layered structures including a Co 2 FeAl/MgO interface have been typical samples studied as PMA-Heusler alloys [19][20][21][22] , and TMR effects using PMA-Co 2 FeAl have also been reported 21,23) . Although a number of studies have been reported for PMA-Co 2 FeAl, or Co 2 FeZ (Z = Al 0.5 Si 0.5 , Si) compounds 24,25) , PMA of other Heulser alloys which contain Mn, such as Co 2 MnSi and relatives have not been studied so much.…”
Section: Introductionmentioning
confidence: 99%
“…The second term corresponds to the damped magnetization precession; B, , , and are amplitude, relaxation time, frequency, and the initial phase of magnetization precession, respectively [17,27]. From a fit to the Kerr rotation spectra, we extracted the values of the and .…”
Section: Resultsmentioning
confidence: 99%
“…12 The most famous p-MTJ has been established successfully with a CoFeB/MgO/CoFeB structure. 13 In addition, a substantial amount of materials have already been studied for the electrodes of p-MTJs, such as L1 0 -FePt 14 [21][22][23][24][25][26] Our group have been focusing on a sort of Co-based full-Heusler alloys, Co 2 (Fe-Mn)Si, for studying PMA and TMR effect. The chemical composition ratio and buffer layer dependence of PMA was investigated systematically in our previous work, [24][25][26] in which it was reported that the thickness of magnetic dead layer of Co 2 (Fe-Mn)Si depends on the buffer layer materials and annealing temperatures, and this was considered to originate from the differences in lattice mismatch and interdiffusion between the buffer layer material and the Co 2 (Fe-Mn)Si layer.…”
Section: Introductionmentioning
confidence: 99%